Resolving the ongoing confusion between Erigeron multiradiatus and Tibetiodes himalaica (Asteraceae) - Bhattacharjee, Avishek; Bhattacharjee, Bandana; Chakraborty, Kasturi; Banu, Farheen; Sherpa, Norbu; Layola M.r., Ranjith (Phytotaxa, 2024)
Erigeron multiradiatus (Asteraceae: Astereae: Conyzinae) and Tibetiodes himalaica (Asteraceae: Astereae: Asterinae) are often misidentified due to their morphological similarity and variation in some morphological characters. The present communication aims to resolve the identity crisis of these two species based on detailed morphological studies of freshly collected as well as herbarium specimens (including types), SEM studies of cypselas and molecular study with one nuclear and one chloroplast marker (ITS and trnLF). The morphological analysis showed that the two species differ in involucres and flower colour, with very clear differences in macro- and micro-morphological features of the cypselas. The molecular study also showed clear distinction between these two taxa. Additionally, a lectotype is designated for Erigeron multiradiatus.